Consolidation of arbitration proceedings - Ahmad Annuar, Muhammad Asraf (2022)
Malaysia has an arbitration system that's commonly used for commercial disputes, and this type of dispute resolution is often utilized for domestic and international matters involving in many industries include the construction industry. There were 125 arbitration cases registered in 2019, and the number of cases started to increase in 2011.Due to the complexity of the industry, there are many parties that are involved in a contract. For example, there are multiple contractors, sub-contractors, and employers who are involved in the construction industry. These parties often have to resolve their disputes through arbitration but not all of them are placed under one consolidation arbitration proceeding. Due to that, there are several issues that are seen as a barrier factor in a consolidation process, especially for cases that occur in Malaysia. Therefore, the purpose of this study is to look at the issues that occur involving consolidation in arbitration proceeding cases which have been brought to the Malaysian Court. Basically, this research process consisted of four major stages, which involved initial study, data collection, data analysis, and completion. The methodology used in this research is document analysis where the cases selected from Lexis Nexis which related to consolidation in arbitration. Based on ten (10) cases involving various industry sectors that have been identified, there are four (4) main issues that are known, which are about instructions issued by the court or arbitrator to carry out consolidation, duplication in consolidation, consolidation without the consent of the parties involved and withdrawal from unification which has contributed to problems in implementing unification in Malaysia. Based on these four (4) factors, the researcher tries to see the reason why the court rejects or accepts an application for consolidation. After analysing the cases, it can be concluded that before the application to conduct consolidation is carried out it is important for each party to identify the main issues in each case to enable consolidation to be carried out and the dispute to be resolved properly. Apart from identifying the main issues in the case, other factors that need to be considered are the parties involved in the consolidation. This is important because it is to avoid any conflict or overlapping cross-actions which can make it difficult for the arbitrator to resolve and this situation can also make the main issue more complex.